2017
DOI: 10.1186/s40623-017-0720-5
|View full text |Cite
|
Sign up to set email alerts
|

Source characteristics of moderate-to-strong earthquakes in the Nantou area, Taiwan: insight from strong ground motion simulations

Abstract: In Taiwan, the Nantou area is a seismically active region where several moderate events have occurred, causing some disasters during the past century. Here, we applied the strong ground motion simulation with the empirical Green's function method to investigate the source characteristics for the eight moderate blind-fault events that struck the Nantou area in 1999 and 2013. The results show that for these Nantou events, a high stress drop and focal depth dependence were noted, which might be related to the imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Relationship of focal depth versus stress drop on SMGA fromWen et al (2017). Dots indicate our results for the 2010 Jiashian and 2016 Meinong earthquakes superimposed on the figureFig.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Relationship of focal depth versus stress drop on SMGA fromWen et al (2017). Dots indicate our results for the 2010 Jiashian and 2016 Meinong earthquakes superimposed on the figureFig.…”
mentioning
confidence: 85%
“…Although the 2010 Jiashian and 2016 Meinong earthquakes were both moderate-sized blind-fault events, the strong ground acceleration reached > 400 gal. Cotton et al (2013) demonstrated that PGA is proportional to stress drop, and Radiguet et al (2009) and Somerville (2003) found that the buried faults strengthen strong ground shaking, especially for a period range of approximately 1 s. Moreover, Wen et al (2017) revealed that moderate blind-fault earthquakes in the Nantou area of Taiwan exhibit focal-depth dependence and a high-stress drop. In this study, we calculated the stress drops in the SMGA for the 2010 Jiashian and 2016 Meinong events and obtained the values of 26.2 and 17.0 MPa (Table 3), respectively; Fig.…”
Section: Strong Ground Shaking Intensified By High-stress Drops Of Dementioning
confidence: 98%